Hedgie's surprise - Brett, Jan, 1949- (New York : G.P. Putnam's Sons, 2000)
Hedgie, the hedgehog, helps Henny, the speckled hen, trick the Tomten who has been eating all of Henny's eggs for breakfast.
AD 550
Adult 550
Accelerated Reader AR
Keywords: Chickens -- Fiction; Hedgehogs -- Fiction; Trolls -- Fiction; Eggs -- Fiction